A not so simplex case of genital herpes. (4th October 2013) - Philip, K E J; Goodman, A; Pallawela, S N S; Sathia, L; Webster, D P
Abstract : We report the case of a 28-year-old, HIV-positive woman presenting with painful vesicular and ulcerating lesions in the ano-genital region caused by varicella zoster virus that appeared similar to herpes simplex infection. The case highlights that herpes zoster needs to be considered in the differential diagnosis of genital lesions, particularly in HIV-positive individuals, and the importance of virological diagnosis by PCR to direct appropriate management.